Impacts of Climate Change on Soil Microbial Interactions: Echoes of the New Normal - Daramola, Fisayo Yemisi; Osemwegie, Osarenkhoe Omorefosa; Ighodaro, Ikponmwosa David; Kioko, Joseph; Lewu, Francis B. (AGRIVITA Journal of Agricultural Science, 2024)
Concerns over the negative impacts of climate change on ecosystems and human life have entered a new phase where many hypothetical views are fast becoming realities. Presently, the rampaging effect of climate change is, in theory, causing ecological catastrophes, and it is being felt at an alarming scale worldwide. As an important ecological niche, the soil ecosystem hosts a diversity of microbiomes and macrobiomes and affords a soil-plant-microbes ecological continuum. Also, it supports essential ecological processes meant to promote life-sustaining habits. However, changes in plant diversity due to increasing greenhouse effects, anthropogenic activities, and global warming have severely impacted the stability of soil microbial communities and interactions, particularly the soil-plant-microbe interaction. A good understanding of the mechanisms underpinning the plant-soil-microbial interactions, the complexity of the soil microbiome, ecosystem adaptability to climate change-induced stresses, and niche functionality of microbiota is necessary for the empirical impact assessment of climate change on soil microbial behaviors. Moreover, the soil system parameters and the various ecological services affected need to be further studied to identify opportunities that could assist the quest to mitigate the debilitating effects of climatic change in the soil ecosystem and sustainable food security initiatives.